Developing a sciencepreneurship-based practical guide by utilizing the local potential of Maluku in science learning - Darwis, Rahmiati; Hardiansyah, Muhammad Rizal; Dewi, Pramita Sylvia (Universitas Islam Negeri Raden Intan Lampung, 2025)
The integration of innovative approaches in science education has become essential in 21st-century learning, particularly in regions with abundant local resources that remain underutilized as educational assets. This research aims to develop and assess the feasibility, practicality, and effectiveness of a sciencepreneurship-based practicum guide integrating Maluku's local potential (lemon cui, cajuput, clove, and gandaria) to enhance students' conceptual mastery. The study employed a Research and Development design using the Borg and Gall model, involving 20 science education students and validation by three experts. Data were analyzed qualitatively through descriptive analysis and quantitatively using N-gain analysis and t-test. Results demonstrated expert validation achieved highly feasible scores (content: 89%, media: 98%, language: 88%), stude nt responses indicated high practicality (89%), and significant effectiveness with N-gain of 0.71 (high category) and significant t-test results (p = 0.023 < 0.05) between pretest (x̄ = 47.75) and posttest (x̄ = 84.75). The developed guide successfully bridges theoretical knowledge with practical entrepreneurial applications, creating meaningful learning experiences that contribute to sustainable development goals and preserve local wisdom.